Association of eating behavior with the nutritional status of high-risk pregnant women admitted to a reference center in the Northeast. - Da Silva, Camila Almeida de Lira; Cecília Santos de Lima, Maria; Josemere de Oliveira Borba, Maria; Cristina de Vasconcelos Martins, Iza; Siqueira de Alemida, Samanta; Liberato de Souza, Anderson; Fidelis Lins Vieira, Nathalia; SILVA AUGUSTO DE ANDRADE, ELDA (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Pregnancy is a period of physical and physiological changes that progresses without complications when free from factors that can compromise maternal and fetal health. Diabetes mellitus, high blood pressure, obesity and inadequate weight gain are the most common causes of gestational risk, and these can be strongly associated with the nutritional status, eating habits and behavior of the pregnant woman. Objective: To describe and associate eating behavior with the nutritional status of high-risk pregnant women admitted to a reference center in the Northeast. Materials and methods: This is a cross-sectional study carried out with patients admitted to high-risk wards at the Instituto de Medicina Integral Prof. Fernando Figueira – IMIP (Recife-PE), anthropometric data and data related to eating behavior were collected (TEMS instrument). Results: Around 56,4% of pregnant women had a prepregnancy BMI classified as overweight or obese, with only 16% classified as underweight. The evaluation of the evolution of weight gain demonstrated that 66.4% had insufficient weight gain, while 12,8% had high gestational weight gain. Discussion: When analyzing eating behavior through the TEMS instrument, the relationship of giving a good image when eating had a significant value (p < 0,05) as well as considerations of choosing healthy foods and related to obtaining energy are directly associated with the current BMI, therefore, note- It is clear that emotional, social, physiological and economic factors influence the choice of food. Conclusion: The high prevalence of overweight and obesity found in this population demonstrates the influence of eating behavior on nutritional status. Reinforcing the importance of preventive measures to identify risk factors and obtain adequate nutritional monitoring during pregnancy with the aim of reducing damage to health and promoting autonomy to make more appropriate and healthy fo